PROFIL CARPAL DAN CUBITAL TUNNEL SYNDROME PADA NELAYAN PESISIR PANTAI MANADO DI MAASING - Linda, Amanda V; Mahama, Corry N; Khosama, Herlyani (FAKULTAS KEDOKTERAN UNSRAT, 2019)
AbstractCarpal tunnel syndrome is a collection of symptoms that occur when the median nerve trapped in the carpal tunnel. Whereas cubital tunnel syndrome is an event of trapping the ulnar nerve in the cubital tunnel and Guyon’s canal. Both syndromes are at the top of the list of cumulative trauma disorders, namely types of musculoskeletal and nervous system injuries due to repetitive work. There had not been much research on carpal and cubital tunnel syndrome, especially in repetitive movements such as fishermen in North Sulawesi. This was a descriptive study that aimed to obtain the profile of carpal and cubital tunnel syndrome in fishermen at Manado coastal specifically in Maasing by using a cross-sectional method. Typical symptoms were assessed based on subjective symptoms; tingling, numbness, pain, or waking up at night. Additional for carpal tunnel syndrome was objective symptoms found in examination of thumb opposition tests, pinprick test, Tinel’s Test, Phalen’s Test, and carpal compression test, and for cubital tunnel syndrome was of Froment sign, elbow flexion test, and Tinel’s test, and whether or not there was sign of Wartenberg. Subjects consisted of 45 persons and the typical symptoms of the syndrome were found in 24 persons; carpal tunnel syndrome in 47% of subjects and cubital tunnel syndrome in 27% of subjects. Typical symptom of carpal and cubital tunnel syndrome mostly found on subject under the age of 50 and work for more than 10 years. Both syndroms showed that paresthesia was the most common symptom.Keywords: carpal tunnel syndrome, cubital tunnel syndrome, fishermen.AbstrakCarpal tunnel syndrome adalah kumpulan gejala yang terjadi saat N. medianus mengalami kompresi di dalam terowongan karpal. Sedangkan cubital tunnel syndrome adalah peristiwa terperangkapnya N. ulnaris di cubital tunnel dan Guyan’s canal. Kedua sindrom ini menempati urutan teratas dalam daftar cumulative trauma disorders yakni jenis cedera muskuloskeletal dan sistem saraf akibat pekerjaan berulang. Belum banyak dilakukan penelitian mengenai carpal dan cubital tunnel syndrome khususnya pada pekerjaan dengan gerakan repetitif seperti pada nelayan di Sulawesi Utara. Metode: Penelitian ini bertujuan untuk mengetahui profil carpal dan cubital tunnel syndrome pada nelayan pesisir pantai Manado di Maasing dengan menggunakan metode potong lintang dan bersifat deskriptif. Gejala khas dinilai berdasarkan gejala subjektif; kesemutan, mati rasa, nyeri, atau terbangun pada malam hari akibat kesemutan di tangan serta gejala objektif hasil pemeriksaan tes oposisi ibu jari, pinprick test, Tinel’s Test, Phalen’s Test, dan carpal compression test untuk carpal tunnel syndrome dan pemeriksaan tes provokasi Froment sign, elbow flexion test, dan Tinel’s test, dan ada maupun tidak ada gejala tambahan berupa Wartenberg sign untuk cubital tunnel syndrome. Subjek yang diteliti berjumlah 45 orang dan sebanyak 24 orang ditemukan adanya gejala khas sindrom; carpal tunnel syndrome pada 47% subjek dan cubital tunnel syndrome pada 27% subjek. Gejala khas carpal dan cubital tunnel syndrome ditemukan lebih banyak pada subjek berusia di bawah 50 tahun dan sudah bekerja selama lebih dari 10 tahun.. Pada carpal dan cubital tunnel syndrome, keluhan yang paling banyak ditemukan adalah kesemutan.Kata kunci: carpal tunnel syndrome, cubital tunnel syndrome, nelayan.